The Realization of Expressive Speech Acts in the Comment Section on Nessie Judge’s YouTube Channel - Urfatul Makhsunah; Hendi Pratama; Frimadhona Syafri (English Education Journal, 2024)
This study aims to analyze the realization of expressive speech acts in the comment section on Nessie Judge's YouTube channel using Searle's theory. Three top conspiracy videos were the object of the research. Data were collected from three selection video comment sections, with comments identified, classified, interpreted, and verified for patterns in expressive speech. Illocutionary Force Indicating Devices (IFIDs) were applied to categorize the comments based on the performative verb of each utterance. The findings categorized the comments into different types of expressive speech acts, such as thanking, apologizing, congratulating, praising, sorrow, and blaming. The analysis revealed that expressions of praising were the most dominant, accounting for 81 utterances. These expressions served to appreciate and acknowledge the quality of the content produced. Several factors contributed to the prevalence of praise, including high video quality, simplifying complex concepts, and fulfilling viewer expectations. Expressions of apology were the least frequent, occurring only 35 times. This study can contribute to education by deepening our understanding of how emotions and attitudes are expressed through language, a crucial aspect of effective communication. This research provides concrete examples of language use in digital contexts by analyzing expressive speech acts in YouTube comment sections. This knowledge can be applied to digital literacy and online communication training, empowering students to navigate and participate in online communities more effectively.